2012
DOI: 10.1293/tox.25.287
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Histological Findings in the Pineal Gland of Crl:CD(SD) Rats

Abstract: To provide background data as the pathologic basis, the pineal glands of 190 male and 193 female Crl:CD(SD) rats at ages of 0–7, 51–58, 70–85 and 111 weeks were examined histologically in this study. Mineralization and fibrosis were common findings in the aged rats, whereas they were rarely found in the young ones; mineralization was present in 7, 44, 67 and 79% of males and in 0, 32, 67 and 79% in females, and fibrosis was present in 0, 29, 48 and 44% of males and 0, 18, 40 and 35% of females at ages of 0–7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…( Allen et al 1982 ; Calvo and Boya 1984 ; Diehl 1978 ; Dill 1963 ; Kristić 1972 ; Prosenc and Cervós-Navarro 1994 ; Tomonari et al 2012 )…”
Section: Pineal Glandunclassified
“…( Allen et al 1982 ; Calvo and Boya 1984 ; Diehl 1978 ; Dill 1963 ; Kristić 1972 ; Prosenc and Cervós-Navarro 1994 ; Tomonari et al 2012 )…”
Section: Pineal Glandunclassified
“…S1). 24 Signal peptide containing proteins that either promote or inhibit mineralization were identified from the human pineal gland. Previous reports have shown that statherin (STATH) maintains calcium and phosphate levels in saliva by inhibiting calcium and phosphate precipitation.…”
Section: Significance Of the Pineal Proteins With Secretory Potentialmentioning
confidence: 99%
“…23 The pineal gland, with aging, contains deposits of calcium, magnesium and phosphates that are known as brain sand or corpora amylacea. 24 It has been reported that the synthesis of melatonin decreases with increase in mineralization of the pineal gland, a process that occurs due to the degeneration of pinealocytes. 25 Mast cells that are immunopositive for tryptase are the key players in the process of calcification in the pineal gland.…”
Section: Introductionmentioning
confidence: 99%
“…We agree that the fibrous material outside of the vacuoles in the top right corner could be collagen fibres. Tomonari et al (2012) investigated 383 rats from a histological viewpoint and found focal…”
Section: Corresponding Authormentioning
confidence: 99%